Peran LBH Kampus di PTKIN dalam Bantuan Hukum terhadap Masyarakat Miskin - Hariyanto Hariyanto (Al-'Adl, 2017)
This study sought to determine the role of two legal aid institutions both based campus in an effort to help the poor in the field of legal assistance in litigation and non litigai. The study covered include the role of LPKBHI IAIN Walisongo and LKBH STAIN Purwokerto, procedures for handling cases in LPKBHI IAIN Walisongo and LKBH STAIN Purwokerto, constraints faced LPKBHI IAIN Walisongo and STAIN Purwokerto LKBH and strategies used to address them.This study uses empirical juridical approach to comparative analysis. The findings of this study indicate that there is a difference between IAIN LPKBHI IAIN Walisongo and LKBH STAIN Purwokerto. Among them are not pure LPKBHI IAIN Walisongo without cost as ordered by Law No. 16 of 2011. LKBH STAIN Purwokerto is still very low in both human resources, finance and facilities. The difference between the two LKBH number of clients are very demanding, indicating that LPKBHI IAIN Walisongo is more widely known by the public, more reliable and better in the role of law to function as a public servant.In that case, both LKBH in principle the same in terms of client service procedures both litigation and non-litigation. But in the actualization, LKBH STAIN Purwokerto still difficulties in maximizing its role as hampered by many constraints both internal and external. While LPKBH IAIN Walisongo, the problem is that the performance of each division's full potential, a lot of managers who served on the faculty, the lack of commitment of some managers. Meanwhile, the strategies used to overcome them; LPKBHI build a wide network of institutions, which resulted in strategic collaborations, the support of institutions that provided the impetus for the pursuit LPKBHI in providing legal assistance. While LKBH STAIN Purwokerto to ask DIPA funds from the campus, asking for help advocate from outside (especially from alumni).